2007
DOI: 10.1111/j.1365-2249.2007.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure as a model for deviation of cytokine responses in experimental Lyme arthritis: HgCl2 treatment decreases T helper cell type 1-like responses and arthritis severity but delays eradication of Borrelia burgdorferi in C3H/HeN mice

Abstract: SummaryLyme borreliosis is a complex infection, where some individuals develop so-called 'chronic borreliosis'. The pathogenetic mechanisms are unknown, but the type of immune response is probably important for healing. A strong T helper cell type 1 (Th1)-like response has been suggested as crucial for eradication of Borrelia and for avoiding development of chronic disease. Many studies aimed at altering the Th1/Th2 balance in Lyme arthritis employed mice deficient in cytokine genes, but the outcome has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The adaptive immune response, particularly humoral response, is important in controlling the severity of Lyme disease in mice, but the bacteria can survive despite eliciting a strong antibody response, possibly because of immune evasion by modulating gene expression. In mice, a stronger initial T-helper type 1 (Th1) response seems to be important for controlling the infection [18,19]. Interestingly, Ixodes tick saliva has been shown to induce a Th2 response that facilitates infection [18,20].…”
Section: The Organism and Pathogenesismentioning
confidence: 98%
“…The adaptive immune response, particularly humoral response, is important in controlling the severity of Lyme disease in mice, but the bacteria can survive despite eliciting a strong antibody response, possibly because of immune evasion by modulating gene expression. In mice, a stronger initial T-helper type 1 (Th1) response seems to be important for controlling the infection [18,19]. Interestingly, Ixodes tick saliva has been shown to induce a Th2 response that facilitates infection [18,20].…”
Section: The Organism and Pathogenesismentioning
confidence: 98%
“…When rats were exposed to aluminum, the level of NE correlated negatively with proportions of CD4 + T lymphocytes, as well as T and B lymphocyte proliferation (Hu et al, 2013), suggesting that an aluminum-induced increase in NE may have an effect on inducing immunosuppression (Hu et al, 2013). However, the neurotoxic effects of these metals on neurotransmission are well characterized (Chang, 1977;Florea and Busselberg, 2006;Lynes et al, 2006) and, therefore, may contribute to some of the immune suppression observed after in vivo exposure to this metal (Dietert et al, 2004;Ekerfelt et al, 2007;Lawrence and Mccabe, 2002;Lee and Dietert, 2003;Lynes et al, 2006;Silbergeld et al, 2005).…”
Section: Synthesis Release and Uptakementioning
confidence: 91%
“…If health-condition is better than before; it shows that all bacteria have been killed. If health is not getting normalize one should refer to some specialist [58].…”
Section: Medication and Prevention Of Diseasementioning
confidence: 99%